Acute effects of foam rolling on cycling performance: A randomized cross-over study - Benvenutti Bueno de Camargo, J.; Barbosa, P. H.; Moraes, M.; Brigatto, F. A.; Batista, D. R.; Hartz, C.; Simoes, R.; Saldanha Aoki, M.; Lopes, C. R. (International Journal of Exercise Science, 2021)
Acute foam rolling protocols may increase range of motion without a negative impact on muscle performance. The main purpose of the present study was to investigate the acute effects of foam rolling on cycling performance (mean power and maximal power), affect and perceived exertion. A secondary aim was to assess the effect of foam rolling on post-exercise muscle soreness. In a random order, ten recreationally trained cyclists (age: 26 ± 5 years; height 1.76 ± 0.06 m; total body mass 78.3 ± 19.8 kg; cycling experience: 5.6 ± 5.3 years; 4.1 ± 1.3 cycling sessions per week and 1.4 ± 1.4 strength sessions per week) were submitted to the following experimental conditions (separated by one week) before performing a three-minute, all-out cycling test: foam rolling or control. During foam rolling protocol, participants were instructed to roll back and forth on one leg and to place the opposite leg crossed over, from the proximal to the distal portion of the rectus femoris and vastus lateralis during one set of sixty seconds for each muscle group. Feeling scale (10 min pre and post-test), CR-10 scale of perceived exertion (ten-minute post-test), pressure pain threshold (pre and 24 h post-test) and mean/maximal power were assessed. No significant differences were observed between conditions for mean and maximal power, affect, perceived exertion, and pressure pain threshold (all p > 0.05). In conclusion, a pre-exercise acute session of self-myofascial release does not improve performance and post-exercise muscle soreness of recreationally trained cyclists.